Extending the Technology Acceptance Model with Scientific Sanad: Evidence from SIAKAD Adoption in Islamic Higher Education - Ade Putra Hayat; Zulfani Sesmiarni; Supratman; Yan Guspriadi; Agung Tri Prasetia (Women, Education, and Social Welfare, 2026)
This study examines students’ acceptance of the Academic Information System Platform (SIAKAD) at the State Islamic Institute (IAIN) Kerinci by extending the Technology Acceptance Model (TAM) with the construct of scientific sanad. Using a quantitative cross-sectional survey design, data were collected from 306 active students selected through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings indicate that students’ acceptance of SIAKAD is generally moderate to high. Attitude Toward Using was the strongest predictor of Behavioral Intention to Use (β = 0.618; p < 0.001), while Sanad Urgency significantly influenced Perceived Ease of Use (β = 0.726; p < 0.001), Perceived Usefulness (β = 1.358; p < 0.001), and Behavioral Intention to Use (β = 0.190; p = 0.008). Conversely, Self-Efficacy showed a significant negative effect on Perceived Usefulness (β = −0.436; p < 0.001). These results suggest that integrating scientific sanad into academic platforms is not merely a technical innovation but also an epistemological need in Islamic higher education. This study contributes to TAM literature by incorporating Islamic scholarly authority into technology acceptance research and offers practical implications for developing a Digital Sanad feature in SIAKAD.